Effect of NaCl and Sorbitol on the Production of Some Alkaloids of Fenugreek Cotyledons Derived Callus - Hassan, Saeb A; Jassim, Emad H (Al-Nahrain Journal of Science, 2018)
Alkaloids often had pharmacological effects. The aim at this study is to increase some alkaloids in fenugreek. Callus induction occurred on cotyledon segments 5 mm long. Murshige and Skoog medium (MS) supplied with 1 mg.lˉ¹ of 2, 4 – D and 0.4 mg.lˉ¹ of kinetin was prepared. The best medium maintained callus was using MS medium supplied with 0.5 mg.lˉ¹ 2, 4-D and 0.5 mg.lˉ¹ kinetin. Callus formation was allowed to take place for a period of thirty days in the dark at 25°C±2. Calli were analyzed using high performance liquid chromatography (HPLC).Methanol callus extract showed high concentrations of some alkaloids compared to the methanol extract of cotyledons. For increasing, the concentration of secondary metabolites, NaCl was added at concentrations 0, 1, 1.5 or 2 g.lˉ¹, sorbitol at concentrations 0, 7, 8 or 9 g.lˉ¹. NaCl at 2 g.lˉ¹ led to significant increase in trigonelline reaching 1354.72 µg per 100 mg fresh weight of callus. NaCl at 1g.lˉ¹ increased choline and carpaine reached 400.82, 483.92 µg.mlˉ¹ per 100 mg respectively. Treatment with 9 g.lˉ¹ sorbitol increased trigonelline and carpaine reached 1666.41, 742.67 µg per 100 mg respectively, while treatment 8 g.lˉ¹ sorbitol significantly increased in choline recorded 588.87 µg per 100 mg.